2010
DOI: 10.4314/bajopas.v2i1.58534
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of re-packaged sweets sold in metropolitan Kano, Nigeria

Abstract: Some readily-available sweet samples comprising of three brands coded A, B and C re-packaged for sale in Kurmi market of metropolitan Kano, Nigeria were microbiologically examined for the load and type of bacteria and fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…The high bacterial count observed in the commercial samples could be attributed to environmental factors (exposure of the samples to soil, air etc. ), type of water used in processing as well as personal hygiene of the handlers [35,36]. It could also be due to microorganisms inherent to the tiger-nut from which the kunun-aya was obtained which later multiply, milling method and milling machine [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The high bacterial count observed in the commercial samples could be attributed to environmental factors (exposure of the samples to soil, air etc. ), type of water used in processing as well as personal hygiene of the handlers [35,36]. It could also be due to microorganisms inherent to the tiger-nut from which the kunun-aya was obtained which later multiply, milling method and milling machine [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The high bacteria count therefore might be as a result of unclean water used in the preparation of the kunu, poor hygienic practice, exposing the kunun-zaki to dust and flies. Improper hand washing after going to the toilet during the preparation of the kunu can also lead to contamination [5], [9], [10]. The percentage of contamination in increasing order showed that Television had highest percentage of 20%, Sabon-Tasha 15%, Mararaban-rido 12.5%, Kujama 7.5% and the lowest was Narayi with 5.0%.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the delicacies particularly among females including students of higher institutions. The presence of microorganisms in food has always been attributed to contamination through water, soil, processing equipment, contact surfaces and the food handlers [9]. Improper handling of food is responsible for most cases of food borne diseases and cross contamination [3].…”
Section: Introductionmentioning
confidence: 99%